Colonial Origins of the Port of Buenaventura - Valencia Llano, Alonso (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article studies the origins of the Port of Buenaventura in the New Kingdom of Granada. It begins with the process of exploration of the coastal territory in order to highlight the different sites in which it was situated, demonstrating that it began as a river port and was later resituated and gradually converted into a maritime port. In addition, this article analyzes the problems it faced, such as the dificulty of communication with the interior of the country, the indigenous resistance that caused the destruction of the town, and inally the necessity of populating the zone with black slaves in order to exploit the mining border. This study also discusses how this port was controlled by the elite of the city of Cali, until the Republican period when it became the sole Colombian port on the Paciic Ocean.